Seismic performance of cantilever retaining wall structure under earthquake loading - Ahmad Lutfi, Mohd Yusof (2016)
Retaining wall structures in Malaysia region are placing more emphasis on lateral earth pressure rather than seismic effect. However, Malaysia actually experienced tremors due to the earthquakes occurred in the neighbouring countries. Therefore, the main objective of this research is to study the behaviour of retaining wall structure under earthquake loading and to determine acceleration and displacement of retaining wall structure during earthquake. Hence, a finite element seismic response simulation of a retaining wall structure using SAP2000 has been presented. Time history, response spectrum and free vibration analysis has been carried out and compared throughout this study. Generally, retaining wall structures in Malaysia region are capable of resisting low seismic activity based on the study. This is happen because the design of retaining wall structures for lateral earth pressure can provide sufficient resistance against potential low seismic effects.